Neurocysticercosis in a Rhesus Macaque (Macaca mulatta) - Johnston, Jessica M (Comp Med, 2016)
An 8-y-old, intact, male rhesus macaque (Macaca mulatta) was sedated to undergo MRI in preparation for the implantation of cranial hardware. During imaging, 9 focal lesions were noted in the brain and musculature of the head. The lesions were hyperechoic with hypoechoic rims. The animal was deemed inappropriate for neuroscience research, and euthanasia was elected. Gross examination revealed multiple round, thick-walled, fluid-filled cysts (diameter, approximately 0.5 cm) in multiple tissues: one each in the left caudal lung lobe, left masseter muscle, and the dura overlying the brain and 8 throughout the gray and white matter of the brain parenchyma. Formalin-fixed sections of cyst-containing brain were stained with hematoxylin and eosin. Microscopic examination and molecular analysis of the COX1 (COI) gene recognized the causative organism as Taenia solium at 99.04% identity.